A Model of the Action of the Shockwave Generated by a Multichannel Discharge on the Union of Bone Tissue with Bone Cement - Zeman, Jan; Hach, Jan; Mikulaková, Wioletta; Derňarová, Ľubica; Eliášová, Anna; Lukeš, Petr; Balážová, Lenka; Beneš, Jiří (In vivo (Athens, Greece), 2016)
BACKGROUND: In reoperation of femoral prostheses, there is a higher percentage of complications associated with the extraction of bone cement from the femoral channel, which is technically and time consumingly tedious. Shockwaves have been used in medicine for years, particularly in urology for the destruction of concretions and orthopaedics, as a method of treating pain in patients with calcifying enthesopathy. MATERIALS AND METHODS: We studied the use of shockwaves generated by a new source based on the multichannel discharge principle in facilitating extraction of bone cement. Femurs of experimental minipigs were chosen as models. We implanted bone cement into the femoral channel and subsequently applied shockwaves. We then measured the force necessary to extract bone cement. RESULTS: The results indicate that the force necessary for extracting cement was consistently statistically significantly lower in the group treated with multichannel discharge shockwaves compared to that for the controls.
Keywords: miniaturní prasata; zvířata; kostní cementy; protézy a implantáty; prasata; femur; Bone and Bones; surgical revision; reoperace; Shockwave; modely u zvířat; Humans; Swine, Miniature; Bone Cements; lidé; kosti a kostní tkáň; rázové vlny s vysokou energií; Animals; Femur; Swine; Prostheses and Implants; High-Energy Shock Waves; Models, Animal; bone cement extractions; Reoperation